2013
DOI: 10.1186/1471-2415-13-24
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery combined with excimer laser trabeculotomy to lower intraocular pressure: effectiveness dependent on preoperative IOP

Abstract: BackgroundCataract surgery combined with excimer laser trabeculotomy (phaco-ELT) can reduce intraocular pressure (IOP). The aim of this study was to evaluate the effect of phaco-ELT on IOP in patients as a function of preoperative IOP.MethodsPatients with open-angle glacuoma or ocular hypertension who received phaco-ELT between 01/2008 and 10/2009 were included. Patients were assigned based on preoperative IOP either to the study group (≤21 mmHg) or control group (>21 mmHg) in this IRB-approved, prospective, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 36 publications
4
32
1
Order By: Relevance
“…Hence, IOP reduction by ELT appears to be effective in both groups, but much more effective in eyes with higher baselirre IOP. This finding has beerr confirmed by a later study [31].…”
Section: El T As a Migs Proceduressupporting
confidence: 71%
“…Hence, IOP reduction by ELT appears to be effective in both groups, but much more effective in eyes with higher baselirre IOP. This finding has beerr confirmed by a later study [31].…”
Section: El T As a Migs Proceduressupporting
confidence: 71%
“…Excimer laser trabeculotomy (or excimer laser trabeculostomy, ELT) ab interno is one of many MIGS techniques [16]. ELT reduces IOP in patients with glaucoma or ocular hypertension [17,18]. Ten laser channels enhance outflow facility through the juxtacanalicular trabecular meshwork (TM) and inner wall of Schlemmʼs canal [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…ELT reduces IOP in patients with glaucoma or ocular hypertension [17,18]. Ten laser channels enhance outflow facility through the juxtacanalicular trabecular meshwork (TM) and inner wall of Schlemmʼs canal [17][18][19][20][21]. ELT is performed with either an endoscopic optics or with a gonio lens, and does not interfere with fistulating surgery should it be necessary at a later time.…”
Section: Introductionmentioning
confidence: 99%
“…No vision-threatening complications were reported. A recent 1-year-study found that patients with a baseline IOP≤21 (mean 16.5 mm Hg) showed a mean IOP decrease of 12% with 1.1 less medications compared to a decrease of 37% on 0.6 less medications in patients with a baseline IOP above 21 (mean 25.8 mm Hg) 46. Long-term failure is typically caused by migration of immediately adjacent47 or remote cell types 48.…”
Section: Resultsmentioning
confidence: 99%